2009
DOI: 10.1016/j.jvs.2009.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Processes of care for carotid endarterectomy: Surgical and anesthesia considerations

Abstract: There are still some vascular surgeons who do not use carotid patching routinely in all patients undergoing CEA, however, based on the data presented in this review, there is Level 1 evidence to support the routine use of carotid patching. Meanwhile, there is no Level 1 evidence to support selective patching for CEA, however a Grade D recommendation may be used to recommend that primary closure can be safely practiced in a large ICA (>6mm). A meta-analysis/systemic review of well-conducted prospective randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…The percentage of restenosis occurring during the first 2 years is of about 0e33% depending on the method of evaluation, definition of restenosis, and time of follow-up. 41 Considering that, it is possible that restenosis could not occur in our cohort. On the other hand, this percentage is not negligible, and the corresponding clinical problem deserves much attention in terms of study of the possible causes.…”
Section: Cfd Analysismentioning
confidence: 93%
“…The percentage of restenosis occurring during the first 2 years is of about 0e33% depending on the method of evaluation, definition of restenosis, and time of follow-up. 41 Considering that, it is possible that restenosis could not occur in our cohort. On the other hand, this percentage is not negligible, and the corresponding clinical problem deserves much attention in terms of study of the possible causes.…”
Section: Cfd Analysismentioning
confidence: 93%
“…7 Another trial by AbuRahma AF, concluded that the perioperative stroke/myocardial infarction and death rates were similar in CEA done under local anesthesia or general anesthesia. 12 The results of (Vassiliou T) clinical trial support the theory that the indication for insertion of intraluminal shunts was significantly reduced by loco-regional anesthesia (14% vs. 43%) due to the more reliable diagnosis of neurological complications. 13 The use of loco-regional anesthesia by itself carries some complications including intrathecal or intravascular injection of local anesthesia, respiratory compromise related to phrenic nerve paralysis, and systemic local anesthetic toxicity if a deep CPB is employed.…”
mentioning
confidence: 67%
“…More importantly, there was no difference in the outcome between LA and GA for patients above the age of 75 years [82].…”
Section: Cea In Elderly Patientsmentioning
confidence: 82%